Perbandingan Insiden Shivering Pasca Operasi dengan Anestesi Umum dan Anestesi Spinal di RSUD Abdul Wahab Sjahranie Samarinda: Comparison of Postoperative Shivering Incidence with General Anesthesia and Spinal Anesthesia at RSUD Abdul Wahab Sjahranie Samarinda - Elsa Syafira Hidayah; M. Rizqan Khalidi; Hary Nugroho (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
One of the most common complications of anesthesia in general and spinal anesthesia is shivering. Shivering may cause discomfort and harm risk towards the patient. This research aims to compare postoperative shivering in patients with general anesthesia and spinal anesthesia. This research is an observational analytic study with cross-sectional approach and was conducted in the recovery room of RSUD Abdul Wahab Sjahranie Samarinda. The sampling method used was total sampling with 69 respondents. Data were obtained using observation sheets and medical records. From 121 patients, the postoperative shivering incidence was more in the underweight group, underwent prolonged surgery, and underwent plastic surgery. The result showed that there was no significant difference between postoperative shivering incidence with anesthetic techniques using chi-square test (p=0,260). Keywords: Comparison, postoperative shivering, recovery room